Multiple Intravenous Injections of Valproic Acid-Induced Mesenchymal Stem Cell from Human-Induced Pluripotent Stem Cells Improved Cardiac Function in an Acute Myocardial Infarction Rat Model. (17th December 2020) - Guo, Shuyuan; Zhang, Yusen; Zhang, Yanmin; Meng, Fanhua; Li, Minghua; Yu, Zhendong; Chen, Yun; Cui, Guanghui
Abstract : Mounting evidence indicates that the mesenchymal stem cell (MSC) injection is safe and efficacious for treating cardiomyopathy; however, there is limited information relating to multiple intravenous injections of human-induced pluripotent stem cell-derived mesenchymal stem cell (hiPSC-MSC) and long-term evaluation of the cardiac function. In the current study, MSC-like cells were derived from human-induced pluripotent stem cells through valproic acid (VPA) induction and continuous cell passages. The derived spindle-like cells expressed MSC-related markers, secreted angiogenic and immune-regulatory factors, and could be induced to experience chondrogenic and adipogenic differentiation. During the induction process, expression of epithelial-to-mesenchymal transition- (EMT-) related gene N-cadherin and vimentin was upregulated to a very high level, and the expression of pluripotency-related genes Sox2 and Oct4 was downregulated or remained unchanged, indicating that VPA initiated EMT by upregulating the expression of EMT promoting genes and downregulating that of pluripotency-related genes. Two and four intravenous hiPSC-MSC injections (10 6 cells/per injections) were provided, respectively, to model rats one week after acute myocardial infarction (AMI). Cardiac function parameters were dynamically monitored during a 12-week period. Two and four cell injections significantly the improved left ventricular ejection fraction and left ventricular fractional shortening; four-injection markedly stimulated angiogenesis reduced the scar size and cell apoptosis number in the scar area in comparison with that of the untreated control model rats. Although the difference was insignificant, the hiPSC-MSC administration delayed the increase of left ventricular end-diastolic dimension to different extents compared with that of the PBS-injection control. No perceptible immune reaction symptom or hiPSC-MSC-induced tumour formation was found over 12 weeks. Compared with the PBS-injection control, four injections produced better outcome than two injections; as a result, at least four rounds of MSC injections were suggested for AMI treatment.